Nonthermal Signatures of Radiative Supernova Remnants. II. The Impact of Cosmic Rays and Magnetic Fields - Rebecca Diesing; Siddhartha Gupta (The Astrophysical Journal)
Near the ends of their lives, supernova remnants (SNRs) enter a “radiative phase,” when efficient cooling of the postshock gas slows expansion. Understanding SNR evolution at this stage is crucial for estimating feedback in galaxies, as SNRs are expected to release energy and momentum into the interstellar medium near the ends of their lives. A standard prediction of SNR evolutionary models is that the onset of the radiative stage precipitates the formation of a dense shell behind the forward shock. In Paper I, we showed that such shell formation yields detectable nonthermal radiation from radio to γ -rays, most notably emission brightening by nearly 2 orders of magnitude. However, there remains no observational evidence for such brightening, suggesting that this standard prediction needs to be investigated. In this paper, we perform magnetohydrodynamic simulations of SNR evolution through the radiative stage, including cosmic rays (CRs) and magnetic fields to assess their dynamical roles. We find that both sources of nonthermal pressure impede shell formation, reducing shell densities by a factor of a few to more than an order of magnitude. We also use a self-consistent model of particle acceleration to estimate the nonthermal emission from these modified SNRs and demonstrate that, for reasonable CR acceleration efficiencies and magnetic field strengths, the nonthermal signatures of shell formation can all but disappear. We therefore conclude that the absence of observational signatures of shell formation represents strong evidence that nonthermal pressures from CRs and magnetic fields play a critical dynamical role in late-stage SNR evolution.